Longitudinal analysis of usage and public awareness of tyrosine kinase inhibitors for CML - Schroer, Adrian E.; Javadi, Tiffany; Mehta, Ankit; Torlak, Furkan; McFarland, Joseph R.; Kumar, Girish; da Silva, Alexandre L.; Benjamin, Jamaal; Choudhary, Moaz M.; Sadeghi, Akram; le Coutre, Philipp; Blaha, Michael J.; et al. (Frontiers in Oncology, 2025)
IntroductionThe treatment landscape of chronic myeloid leukemia (CML) has evolved with the introduction of second- and third-generation tyrosine kinase inhibitors (TKIs), oCering potential advantages over imatinib. We analyzed prescription trends and public awareness of TKIs to assess the adoption of newer agents.MethodsMonthly US prescription data from the IQVIA National Prescription Audit (NPA) and Google Trends search volumes from March 1, 2017, to November 31, 2024, were analyzed for visual and quantitative trends and correlation patterns. Studied TKIs included imatinib (first generation), dasatinib, bosutinib, nilotinib (second generation), and ponatinib, asciminib (third generation).ResultsSecond-generation TKIs increased by 14.4% (15,171 to 17,363 average monthly prescriptions) between 2017 and 2024, while the use of imatinib declined (-10.0%, from 18,704 to 16,835). Bosutinib (+144.1%) and dasatinib (+27.8%) usage increased during this period, while nilotinib prescriptions decreased (-26.0%). Third-generation TKIs saw substantial growth (696 to 2,123 average monthly prescriptions), led by ponatinib (+86.6%) and asciminib (+235.0% since 2022). Online search volumes strongly correlated with prescription trends, particularly for newer TKIs: asciminib (r = 0.85), bosutinib (r = 0.74), nilotinib (r = 0.74), ponatinib (r = 0.63), and dasatinib (r = 0.51). Imatinib showed little correlation (r = 0.21). Prescription patterns varied across disciplines, with Advanced Practice Providers (APPs) prescribing imatinib 9% less frequently than internists/primary care physicians (PCPs).DiscussionThese data highlight a shift toward newer TKIs in CML treatment, mirroring guideline recommendations and rising public awareness. Online search trends complement traditional prescription monitoring, oCering near real-time insights into evolving prescribing practices and drug adoption.